Pengaruh Karakteristik Individu dan Iklim Organisasi Terhadap Kepuasan Kerja Serta Implikasinya Pada Prestasi Kerja Karyawan PT PLN (Persero) Uiw S2jb Up3 Lahat - Yulanda, Delvina (MOTIVASI, 2020)
Purpose – The purpose of this research are to identify and analyse the influence of the individual characteristics and organization climate on job satisfaction and its impact on employee performance of PT. PLN (Persero) Region-S2JB Branch Lahat..Design/methodology – This research takes 107 people as a sampling that conducted by census. Data analysis was performed with the Structural Equation Model (SEM) using Lisrel software.Findings - There are positives and significants effect in partially and simultaneously of individual characteristics variable and organization climate on job satisfaction and its impact on employee performance. Individual characteristics have dominant influence on job satisfaction and its impact to employee performance. The implications of managerial can suggestion to increase employee performance with increase individual characteristics, organizational climate, and job satisfaction of employee. To increase individual characteristics, its can give interpersonal skill training and placement employee according their skill, to increase organizational climate with repairing work tools, and to increase job satisfaction, it can give training of leadership for chairman.